Mečys Mačernis in the didactics of mathematics - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2012)
Mečys Mačernis (1897–1968) taught elementary Mathematics and Didactics at the Republican Pedagogical Institute of Klaipėda during the years 1935–1939. He studied at universities of Berlin and Königsberg, during the period of time from 1926 to 1934 he worked as a head master of teachers’ seminary in Tauragė. In 1935–1935 M. Mačernis worked as a vice-director of the Republican Pedagogical Institute of Klaipėda and since 1937 he worked there in the position of a director. Even in 1926 for students of the Teachers’ seminary, he published a methodical textbook of teaching Arithmetics. During 1925–1928 he published 3 articles about mathematics didactics. During his activity in Klaipėda, M. Mačernis prepared and in 1940 published for students of the institute a methodical textbook of teaching Arithmetics and Geometry. In 1938–1939 he completed a work about pedagogy of the Middle Ages and a large, three volume work titled ‘Didactics’. Together withthe Institute, M.Mačernis left Klaipėda that was separated from Lithuania by Hitler and went to Panevėžys, and later to Vilnius that was returned back to Lithuania. When Lithuania was occupied by the Bolsheviks, M. Mačernis was dismissed from the director position. In 1941 he was arrested and deported to far inland Russia. After the World War II he worked as a teacher of Mathematics in the Karaganda region. When M. Mačernis returned to Lithuania after deportation, he worked as a teacher of Mathematics at school in Plungė. After the year 1940 M. Mačernis did not write any scientific pedagogical work. Methodical textbooks of teaching Mathematics written by M. Mačernis presented the teachers of Lithuania actual ideas of connections established between teaching and practice, internal and inter-subjective integration that were widely discussed in Western Europe of that time.
Keywords: mathematics didactics; textbook; articles